Q: 6(x - 1) + 3x + 2
A.
9x - 8
B.
-3x - 4
C.
9x + 8
D.
9x - 4
can you show me how to solve this?

A: 6(x - 1) + 3x + 2 = 6x + - 6 + 3x + 2 =(6x + 3x) + (-6 + 2) = 9x + - 4 = 9x - 4

Expert answered|cjam_1977|Points 200|

Question|Rated good

Asked 5/14/2012 8:38:08 PM

Updated 9/4/2014 6:58:35 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by jeifunk [9/4/2014 6:58:34 AM]

Rating

3

6(x - 1) + 3x + 2

= 6x + - 6 + 3x + 2

=(6x + 3x) + (-6 + 2)

= 9x + - 4

= 9x - 4

= 6x + - 6 + 3x + 2

=(6x + 3x) + (-6 + 2)

= 9x + - 4

= 9x - 4

Added 9/4/2014 6:58:35 AM

This answer has been confirmed as correct and helpful.

0 + 5 = 5
A.
commutative property of multiplication
B.
identity property of addition
C.
commutative property of addition
D.
identity property of multiplication
**Weegy:** 0 + 5 = 5 is an Identity property of addition. (More)

Question

Expert Answered

Updated 6/22/2015 1:29:17 PM

0 Answers/Comments

-5 - 8x = -3x
A.
x = 25
B.
x = -25
C.
x = 1
D.
x = -1
**Weegy:** -5 - 8x = -3x
-8x + 3x = 5
-5x = 5
x = 5/-5
x = -1 (More)

Question

Expert Answered

Updated 165 days ago|1/4/2018 5:30:50 AM

0 Answers/Comments

8.2 + (–8.2) = 0
A.
Inverse Property of Addition
B.
Addition Property of 0
C.
Identity Property of Addition
D.
Inverse Property of Multiplication
**Weegy:** D. Inverse Property of Multiplication
(More)

Question

Expert Answered

Updated 5/14/2014 12:49:39 AM

1 Answer/Comment

Visual acuity is your ability to see colors clearly.
A.
true
B.
false

Question

Not Answered

Updated 32 days ago|5/18/2018 4:34:35 AM

1 Answer/Comment

26,995,957 questions answered

There are no comments.